2020
DOI: 10.4314/ljh.v31i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic undercurrent and macro-level determinants of voter participation in Ghana’s 2012 election: Implications for the 2020 national elections

Abstract: In this paper we analyze the ethnic undercurrent and macro-level determinants influencing voter participation in Ghana based on aggregate district-level data. The paper focuses on the determinants that influenced citizens’ political participation in the 2012 Presidential elections of the Fourth Republic of Ghana and their implications for the December 2020 national elections. The unique approach of this paper is that district-level aggregate data on economic characteristics compiled by the Ghana Statistical Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Regardless of the perspective from which the debate is anchored, it is evident that neither argument can be convincingly maintained, as the predicament faced by developing nations such as Ghana does not allow for a singular choice to be made. The challenge of political and economic progression in a majority of these countries, including Ghana, demands concurrent consideration of political, sociocultural, and economic factors and issues (Bukari, 2017, Anaman & Bukari, 2019a, 2019b, 2022Anaman, 2016;Alidu & Bukari, 2020;Anaman & Bukari, 2021). This paper aligns with the view that political and economic liberation should be pursued concurrently and that prioritizing one over the other from the outset is inherently flawed.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Regardless of the perspective from which the debate is anchored, it is evident that neither argument can be convincingly maintained, as the predicament faced by developing nations such as Ghana does not allow for a singular choice to be made. The challenge of political and economic progression in a majority of these countries, including Ghana, demands concurrent consideration of political, sociocultural, and economic factors and issues (Bukari, 2017, Anaman & Bukari, 2019a, 2019b, 2022Anaman, 2016;Alidu & Bukari, 2020;Anaman & Bukari, 2021). This paper aligns with the view that political and economic liberation should be pursued concurrently and that prioritizing one over the other from the outset is inherently flawed.…”
Section: Introductionmentioning
confidence: 81%
“…The analysis draws on data from a random sample of 600 individual voters residing in Ghana's four most pivotal electorally swing constituencies. The study seeks to unpack an array of the political economy matters associated with election and perceived individual and communal socio-economic ramifications within the Agona East, Effutu, Sunyani, and Techiman North constituencies (Bukari, 2017;Anaman & Bukari, 2019a, 2019b, 2021Alidu & Bukari, 2020;Bukari, 2022).…”
Section: Study Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The era from February 24, 1966, to January 7, 1993, witnessed a significant level of political instability characterised by a series of both successful and unsuccessful military coups. It was during this period that the Fourth Republican Constitutional System was introduced (Bukari, 2017;Alidu & Bukari, 2020;Anaman & Bukari, 2021;Bukari, 2022;Bukari et al, 2022a&b;Mbowura et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Ghana, has demonstrated that owing to the scarcity and ambiguity of political information, voters tend to resort to social identities, particularly ethnicity, for heuristic cues on how to vote. Others also argued that being aware of the influence of socio-ethnic identity, personal linkages and clientelism, Ghanaian leaders often resort to ethnic identities as the basis for forming political voters and mobilising support for their parties, and the cycle continues (Alidu & Bukari, 2020;Adams, Agomor & Youmbi, 2018). What this means is that the vital element that shapes the decision and electoral choice of the citizens is dependent on socio-cultural and ethnic reasoning without taking into account the relevance of policy alternatives.…”
Section: Introductionmentioning
confidence: 99%